Anti-inflammatory Approach With Early Double Cytokine Blockade (IL-1β and TNF-α) Is Safe and Facilitates Engraftment in Islet Allotransplantation. Issue 3 (March 2020) - Onaca, Nicholas; Takita, Morihito; Levy, Marlon F.; Naziruddin, Bashoo
Abstract : Background: The approach to reducing nonspecific inflammation after islet allotransplantation has been designed to improve engraftment, typically using 1 agent. We report results with the use of combination inflammatory blockade consisting of anti-interleukin (IL)-1β and tumor necrosis factor (TNF)-α. Methods: Nine patients underwent islet allotransplantation under a prospective research protocol using double cytokine blockade with anti–TNF-α (etanercept, d 0, 3, 7, 10) and IL-1β (anakinra, d 0–7) at the time of each islet infusion. The primary endpoint, assessed 2 years after the last islet transplant, was the elimination of severe hypoglycemic events and hypoglycemia unawareness, with proper glycemic control, and detectable serum C-peptide. Results: No thrombotic events or infectious complications were associated with combined IL-1β and TNF-α blockade. Six patients became insulin independent, 2 had partial function, and 1 had primary nonfunction. After 24-month follow-up, 6 of 9 patients had excellent glycemic control, hemoglobin A1c ⩽6.5%, and no episodes of hypoglycemia unawareness. Eight patients developed HLA alloantibodies at various time points (class 1, 5; class 2, 6), with enhanced T-cell alloreactivity. One patient retained good graft function despite having anti-glutamic acid decarboxylase 65 antibodies. Conclusions: The use of double cytokine blockade is safe, with reduction of inflammation at transplantation and presumably with better engraftment. However, it does not influence later islet loss from T-cell–mediated autoimmunity and alloimmunity, which require other strategies to maintain long-term islet function. Abstract : Supplemental Digital Content is available in the text.